Comportamiento de clones de caccao (theobroma cacai L.) de selecciones avanzadas de varios cruzamientos en la zona de Quevedo. - Benavides Vera, Jorge Ismael (2014)
This work was performed at the Experimental Station of Tropical Pichilingue lNlAP. The research aims to identify the best cocoa clones agronomic behavior and sensory advanced selections from several crosses, particularly those related to health and productivity and sensory analysis. 42 clones were evaluated from cross between parental National CCN -51 and Nacional x , including two witnesses EET- 103 and CCN -51 . Numbers of healthy ears , fresh weight (kg ) , number of diseased pods , numbers of diseased pods with moniliasis, Fruits to wilt ( Cherelles Wilt ) , number of vegetative brooms : Between January and December 2013 period data for the following variables were recorded and bearings, seed index and index cob, sensory analysis. All variables will be subjected to analysis of variance and Tukey test at 0.05 probability of error ( or 0.95%) confidence probability for statistical difference between the means . The results obtained correspondingly variable numbers to healthy ears during the year T12 clones ( EET- 446 x E2/T9/R2/A8 CCN -51 ) and T28 (CCN -51 x - 21-29 CCAT E1/T11/R4 / A4 ) highlighted with 39 ears . The yield of dry cocoa he got the clone T28 ( EET- 446 x -51 E2/T9/R2/A8 CCN ) which highlighted the highest average yield at 1.27 (Kg / tree). The combination of the higher rates of ear and seed variables was observed in clones T2 ( EET- 454 EET- 400 E1/T15/R4/A1 x ) , T20 ( CCN- EET- 387 51 x E4/T8/R5/A4 ) Testigo2 (CCN -51 ) , T29 ( EET- 426 x E2/T2/R1/A3 CCN -51 ) , T34 ( CCN- EET- 534 51 x E5/T5/R2/A2 ) Testigo1 ( EET- 103 ) , T33 (CCN -51 x E5/T5/R3/A1 EET- 462 ) with 15 and 1.24 , 16 and 1.62 , 16 and 1.29 , 18 and 1.70 , 21 and 1.58 , 21 and 1.45 , 23 and 1.85 on your order . The average fruit accumulated sick fluctuated between 1.5 and 23.5 , with lower incidence won the T22 clone (CCN -51 x -387 E4/T8/R1/A4 EET ) , this treatment being obtained by the minimum average monillas ears . Regarding the T39 sensory analysis (CCN -51 x E5/T4/R4/A3 EET- 450 ) and T35 (CCN -51 x E5/T3/R1/A15 EET- 416 ) clones appears to be more moderate to a comprehensive sensory balance more in line with the requirements of the industry.